Defining local extreme heat thresholds and Indoor Cooling Degree Necessity for vulnerable residential dwellings during the 2020 summer in Ankara – Part I: Air temperature. (August 2022) - Santos Nouri, A.; Çalışkan, O.; Charalampopoulos, I.; Cheval, S.; Matzarakis, A.
Graphical abstract: Highlights: New heat thresholds were defined to identify exposure to local heat events. Extreme heat impacts linked to thermally vulnerable residential dwellings. First Indoor Cooling Degree Necessity metric was prepared to define indoor heat stress. Indoor conditions revealed high exposure to the newly defined extreme heat thresholds. Abstract: This study discusses the preliminary assessment of I ndoor C ooling D egree N ecessity (ICDN) based upon the standard air temperature (Ta) value of 22 °C which is defined to be the standard upper mean temperature limit (Tl ) for interior comfort as defined by the WHO. By considering indoor air temperature (TaI ), levelled oscillations above Tl are utilised to determine indoor temperature extremes/frequencies at a 10 min temporal resolution during the months of July and August 2020 in Ankara. These recordings were undertaken through the use of an interior in-situ Meteorological Station (MS), simultaneously, an outdoor in-situ MS was also mounted outside the naturally ventilated dwelling with the identical measurement interval period. Moreover, to supplement the encompassing outdoor data collection, two WMO MSs were utilised in the study to account for both encompassing local peri -urban Esenboga (EMS) and Ankara's urban (AMS) outdoor air temperatures (TaO ) at a 1 h temporal resolution. In addition to the ICDN's identified variation of Tl levels, which frequently remained between +7 °C and +10 °C during periods of accentuated urban outdoor heat stress; their direct/latent cause-and-effect relationship with newly defined local extreme heat thresholds were established. Relative to July and August 2020, a total of 19 Very Hot Days (VHD33 ), 10 Monthly Tropical Night (MRT20 ), and 4 Heatwave Events (HWE31 ) were determined. These thresholds further underlined the growing need to associate indoor and outdoor heat stress during local extreme heat events, particularly in more vulnerable residential contexts; and moreover, in an era of increasing heat stress as result of rapid urbanisation and climate change.